Isolation of leptospira spp. and serological diagnoses in patients with acute febrile illness in Hospital Universiti Sains Malaysia - Mohamad, Amira Wahida (2018)
Leptospirosis is an acute febrile illness and re-emerging disease that occurs worldwide and most incidence in tropical countries such as Malaysia. Leptospirosis is caused by the pathogenic Leptospira species. The disease is maintained in the nature by chronic renal infection of reservoir host particularly rodents and human transmission occurs through indirect or direct contact with the urine of infected animals. Leptospirosis is difficult to diagnose because of the unspecific symptoms and serological tests results that need to be interpreted carefully. There is much overlap in the clinical presentation of undifferentiated febrile illnesses, which includes leptospirosis, malaria, rickettsioses, and arboviral diseases, it is not possible to reliably predict the pathogen based on clinical signs and symptoms. Therefore, the aim of this study is to isolate the Leptospira spp. and to perform serological diagonoses from patients with acute febrile illness in Hospital Universiti Sains Malaysia (HUSM). This is a cross sectional descriptive study. All patients (n= 109) were recruited from the emergency department of HUSM with the symptoms of acute febrile illness. The blood samples were taken and inoculated in the modified Ellinghausen McCullough Johnson Harris (EMJH) media with addition of different concentration of 5-Fluorouracil. The cultures were incubated in incubator shaker at 30°C for 6 months and examined weekly under dark-field microscopy for presence of Leptospira. Serology tests which were immunochromatography test (ICT) and microscopic agglutination test (MAT) were carried out to determine the presence ofspecific antibodies against Leptospira in the recruited patients. The positive cultures were amplified and identified by PCR on 16S rRNA gene by sequencing. The presence of the pathogenic genes also was determined by using nine pathogenic genes which are lfb1, flaB, OmpL1, ligA, ligB, ligC, lipL21, lipL32 and lipL4. A total of 109 samples from patients whose seek treatments at emergency department of HUSM were collected. Based on microscopic observation under dark field microscope, 1.85% (n= 2/109) of the samples were positive with Leptospira isolation which were labelled as B004 and B208. Only 2.75% (n=3/109) were positive when tested with ICT. All samples with positive and intermediate ICT tested with MAT were all negative. In addition, sample with positive culture (B004) was tested negative for ICT meanwhile, B208 was tested intermediate with ICT and negative with MAT. Isolates B004 and B208 were identified by 16S rRNA as Leptospira interrogans and Leptospira weilli respectively. Both of the isolates were classified under pathogenic Leptospira and were determined by the presence of nine and five pathogenic genes respectively. The constructed phylogenetic tree confirms the genetic relationships between the two species which arised from different species under pathogenic group. The optimization of different culture supplementation and type of samples were conducted by using different type of serovars for isolation improvements. The results showed whole blood and EMJH without addition of others supplement were the best among others which were human serum and rabbit serum. In conclusion, two pathogenic Leptospira isolates were successfully cultivated from patients with acute febrile illness in HUSM and both were characterized by nine pathogenic genes. Further study with comprehensive approaches need to be conducted to improve the isolation rate and molecular study could be more explored.